Ethical Issues in Cyborg Technology: Diversity and Inclusion. - Park, Enno (NanoEthics, 2014)
Progress has reached the point where cyborg technology is leaving the sphere of mere science fiction. Whereas society as a whole formed a symbiosis with technology long ago, individuals are now starting to merge with technology as well. The effects can already be studied by looking at the examples of smartphones, computers and the Internet. The idea of 'repairing' humans, medical implants more sensitive than our natural, human faculties and even non-medical implants raise a lot of ethical questions, and require the concept of inclusion to be re-thought.